2018
DOI: 10.1111/imj.13554
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label use of rituximab in autoimmune disease in the Top End of the Northern Territory, 2008–2016

Abstract: Rituximab has been used off-label for a range of autoimmune diseases in this population with a high proportion of Aboriginal patients successfully and safely in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…However, the infection rate went up to 25% in NHPs under anti‐CD 20 Ab/tacrolimus regimen, although the difference was not statistically significant. Our triple immunosuppressant regimen (anti‐CD 20 Ab/tacrolimus/basiliximab) showed comparable safety with that described in a previous report, which presented a 27.3% bacterial or protozoal infection rate in patients who received anti‐CD20 Ab …”
Section: Discussionsupporting
confidence: 72%
“…However, the infection rate went up to 25% in NHPs under anti‐CD 20 Ab/tacrolimus regimen, although the difference was not statistically significant. Our triple immunosuppressant regimen (anti‐CD 20 Ab/tacrolimus/basiliximab) showed comparable safety with that described in a previous report, which presented a 27.3% bacterial or protozoal infection rate in patients who received anti‐CD20 Ab …”
Section: Discussionsupporting
confidence: 72%
“…1,4−6 The safety and e cacy of rituximab in the Top End of Northern Territory was examined in a retrospective descriptive study examining the off-label use of rituximab in patients with autoimmune diseases. 35 The authors of the study reported 18 episodes of infection in 66 patients, of whom, 41(62.1%) self-identi ed as Indigenous Australians. 35 A 'clinically signi cant response' was seen in 3 of the 4 patients treated for Lupus Nephritis.…”
Section: Discussionmentioning
confidence: 97%
“…35 The authors of the study reported 18 episodes of infection in 66 patients, of whom, 41(62.1%) self-identi ed as Indigenous Australians. 35 A 'clinically signi cant response' was seen in 3 of the 4 patients treated for Lupus Nephritis. Accepting the limitations of retrospective study and the inconsistent documentation of objective disease activity, the authors concluded that off-label use of rituximab for treatment of autoimmune diseases is common and safe in majority of cases.…”
Section: Discussionmentioning
confidence: 97%
“…Fourteen references [10,14,[28][29][30][31][32][33][34][35][36][37][38][39] published between 1999 and 2018, were included. At least one study was conducted in each Australian state or territory with the exception of the ACT and Tasmania.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Fourteen studies focused on certain populations including pregnant women [31], paediatric patients [10,14,32]. palliative care patients [29,30] and patients with dermatological conditions [33], psychiatric disorders [34] and autoimmune or other conditions [30,[35][36][37][38][39].…”
Section: Review Of the Literaturementioning
confidence: 99%